Characteristics of US Health Care Providers Who Counsel Adolescents on Sports and Energy Drink Consumption - Nan Xiang; Holly Wethington; Stephen Onufrak; Brook Belay (Hindawi Limited, 2014)
Objective. To examine the proportion of health care providers who counsel adolescent patients on sports and energy drink (SED) consumption and the association with provider characteristics. Methods. This is a cross-sectional analysis of a survey of providers who see patients ≤17 years old. The proportion providing regular counseling on sports drinks (SDs), energy drinks (EDs), or both was assessed. Chi-square analyses examined differences in counseling based on provider characteristics. Multivariate logistic regression calculated adjusted odds ratios (aOR) for characteristics independently associated with SED counseling. Results. Overall, 34% of health care providers regularly counseled on both SEDs, with 41% regularly counseling on SDs and 55% regularly counseling on EDs. On adjusted modeling regular SED counseling was associated with the female sex (aOR: 1.44 [95% CI: 1.07-1.93]), high fruit/vegetable intake (aOR: 2.05 [95% CI: 1.54-2.73]), family/general practitioners (aOR: 0.58 [95% CI: 0.41-0.82]) and internists (aOR: 0.37 [95% CI: 0.20-0.70]) versus pediatricians, and group versus individual practices (aOR: 0.59 [95% CI: 0.42-0.84]). Modeling for SD- and ED-specific counseling found similar associations with provider characteristics. Conclusion. The prevalence of regular SED counseling is low overall and varies. Provider education on the significance of SED counseling and consumption is important.